Dielectric anisotropy and electrical properties of the copper phthalocyanine (CuPc): 4-4?-n-Heptylcyanobiphenyl (7CB) composite liquid crystals - Al-Hazmi, Faten; Al-Ghamdi, Ahmed A.; Al-Senany, Noruh; Alnowaiser, Fowzia; Yakuphanoğlu, Fahrettin (Elsevier Sci Ltd, 2014)
Dielectric anisotropy and electrical properties of the copper phthalocyanine (CuPc): 4-4'-n-heptylcyanobiphenyl (7CB) composite liquid crystals have been investigated. Liquid crystals exhibit dielectrically-controlled positive dielectric anisotropy (p-type Delta epsilon) and the dielectric anisotropy changes from positive to negative dielectric anisotropy (n-type Delta epsilon) behavior with frequency of applied electrical field. The critical frequency f(c) values for the 7CB and CuPc doped 7CB liquid crystals were found to be 602 kHz and 518 kHz, respectively. This indicates that CuPc doping causes a decrease in the critical frequency. The splay elastic coefficients of the 7CB and CuPc doped 7CB liquid crystals were determined and CuPc doping increases the splay elastic coefficient of 7CB liquid crystal. The 7CB liquid crystal exhibits a voltage-controlled differential negative resistance (VCNR) behavior and CuPc doping affects significantly VCNR behavior of 7CB. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Electrical properties; Physical properties; Anisotropy